2022
DOI: 10.1021/acsomega.2c02638
|View full text |Cite
|
Sign up to set email alerts
|

Using Lifetime and Quenching Rate Constant to Determine Optimal Quencher Concentration

Abstract: Excited state quenching is a key step in photochemical reactions that involve energy or electron transfer. High reaction quantum yields require sufficiently high concentrations of a quencher to ensure efficient quenching. The determination of quencher concentrations is typically done through trial and error. Using kinetic modeling, however, a simple relationship was developed that predicts the concentration of quencher necessary to quench 90% of excited states, using only the photosensitizer lifetime and the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…45−48 We also recently demonstrated that experimental quencher concentrations for short-lived, organic photocatalysts are often much too low to ensure efficient quenching and therefore will lead to low QY. 49 It is also important to emphasize that the QY in Figure 1 is an external QY. Our recent work on the coupling of 1,4-dicyanobenezene and N-phenylpyrrolidine showed that while the internal QY of the reaction was close to 1 at early times, because of parasitic light absorption and scattering losses, the external QY was 0.3 or less.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…45−48 We also recently demonstrated that experimental quencher concentrations for short-lived, organic photocatalysts are often much too low to ensure efficient quenching and therefore will lead to low QY. 49 It is also important to emphasize that the QY in Figure 1 is an external QY. Our recent work on the coupling of 1,4-dicyanobenezene and N-phenylpyrrolidine showed that while the internal QY of the reaction was close to 1 at early times, because of parasitic light absorption and scattering losses, the external QY was 0.3 or less.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In general, extremely low QY are not an unrealistic possibility as reports of QY on the order of 0.01 or less are common in the literature. We also recently demonstrated that experimental quencher concentrations for short-lived, organic photocatalysts are often much too low to ensure efficient quenching and therefore will lead to low QY . It is also important to emphasize that the QY in Figure is an external QY.…”
Section: Resultsmentioning
confidence: 99%
“…14 Organic photocatalysts have also received significant attention due to the lack of precious metals and ability to drive a wide range of transformations; however, many of these photocatalysts exhibit shorter excited-state lifetimes, and care must be taken in reaction design. 15,16 Careful design of the radical-generating SET event is necessary when developing photocatalytic transformations. 17,18 Depending on the mechanism of quenching, the SET event generates a radical cation or radical anion intermediate, which are inherently less stable than their neutral counterparts.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Visible light photocatalysis is used to drive different types of small-molecule, bond-forming transformations. Photocatalytic transformations harness the oxidation or reduction potential of short-lived excited states that can undergo single electron transfer (SET) via reductive or oxidative quenching of the excited state to generate radical intermediates in redox-labile substrates. Often, transition metal photocatalysts, like tris(2-phenylpyridine)iridium(III) (Ir(ppy) 3 ) or tris(bipyridine)ruthenium(II) chloride ([Ru(bpy) 3 ] 2+ ), are used because of their long-lived excited states, good visible light absorption, and tunable reduction potentials . Organic photocatalysts have also received significant attention due to the lack of precious metals and ability to drive a wide range of transformations; however, many of these photocatalysts exhibit shorter excited-state lifetimes, and care must be taken in reaction design. , …”
Section: Introductionmentioning
confidence: 99%